2012
DOI: 10.1186/1472-6963-12-256
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the care transition measure in multi-ethnic South-East Asia in Singapore

Abstract: BackgroundThe 15-item Care Transition Measure (CTM-15) is a measure for assessing the quality of care during transition from the patients’ perspective. The purpose of this study was to test the psychometric properties of the CTM-15 and CTM-3 (a 3-item version of the CTM-15) in Singapore, a multi-ethnic urban state in South-east Asia.MethodsA consecutive sample of patients was recruited from two tertiary hospitals. The subjects or their proxies were interviewed 3 weeks after discharge from hospital to home in E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
29
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 24 publications
7
29
2
2
Order By: Relevance
“…The J‐CTM‐15 was found to comprise 3 factors, demonstrating a different structure when compared to the original factor model, which is similar to the finding of previous studies conducted in Singapore and Israel . Factor 2 was composed of items such as “Self‐management support” and “Patient and caregiver preparation.” In the Japanese version, Factor 2 labeled “Understanding and confidence of self‐management” was different from the factor “Critical understanding” and “Management preparation,” which were proposed in the original CTM‐15.…”
Section: Discussionsupporting
confidence: 68%
“…The J‐CTM‐15 was found to comprise 3 factors, demonstrating a different structure when compared to the original factor model, which is similar to the finding of previous studies conducted in Singapore and Israel . Factor 2 was composed of items such as “Self‐management support” and “Patient and caregiver preparation.” In the Japanese version, Factor 2 labeled “Understanding and confidence of self‐management” was different from the factor “Critical understanding” and “Management preparation,” which were proposed in the original CTM‐15.…”
Section: Discussionsupporting
confidence: 68%
“…The results revealed that the transitional care received by the study population was suboptimal compared with studies in USA and Singapore using the same measure and another study in Canada using a different measure (the total CTM score in the present study was 42.2 compared with a total score of 66.0 in Singapore, 67.34 in USA, and a mean score percentage of 80.8 in Canada) [12,14,15]. The present study aimed to assess the quality of transitional care at one HIO hospital in Egypt from the patients' perspective using the CTM.…”
Section: Discussioncontrasting
confidence: 61%
“…As for the dimension concerning patients' agreement on care plans, the total score was 33.5 compared with scores of 66.6 and 67.2 in two studies conducted in Singapore and USA, respectively [12,14]. This could be explained by the desire of healthcare providers to maintain control, lack of time and lack of training in skills of providing a patientcentered care in the current study setting.…”
Section: Discussionmentioning
confidence: 69%
“…La Care Transmision Measure ha sido validada y utilizada con éxito en entornos lingüísticos y culturales diferentes al anglosajón (5,12,14,15), si bien no se han encontrado estudios que se hayan centrado en las características psicométricas de la encuesta en español.…”
Section: Discussionunclassified